Lung dendritic-cell metabolism underlies susceptibility to viral infection in diabetes - Nobs, Samuel; Kolodziejczyk, Aleksandra A.; Adler, Lital; Horesh, Nir; Botscharnikow, Christine; Herzog, Ella; Mohapatra, Gayatree; Hejndorf, Sophia; Hodgetts, Ryan-James; Spivak, Igor; Schorr, Lena; Fluhr, Leviel; et al. (Nature, 2023)
Abstract -People with diabetes feature a life-risking susceptibility to respiratory viral infection, including influenza and SARS-CoV-2 (ref. - 1 -), whose mechanism remains unknown. In acquired and genetic mouse models of diabetes, induced with an acute pulmonary viral infection, we demonstrate that hyperglycaemia leads to impaired costimulatory molecule expression, antigen transport and T cell priming in distinct lung dendritic cell (DC) subsets, driving a defective antiviral adaptive immune response, delayed viral clearance and enhanced mortality. Mechanistically, hyperglycaemia induces an altered metabolic DC circuitry characterized by increased glucose-to-acetyl-CoA shunting and downstream histone acetylation, leading to global chromatin alterations. These, in turn, drive impaired expression of key DC effectors including central antigen presentation-related genes. Either glucose-lowering treatment or pharmacological modulation of histone acetylation rescues DC function and antiviral immunity. Collectively, we highlight a hyperglycaemia-driven metabolic-immune axis orchestrating DC dysfunction during pulmonary viral infection and identify metabolic checkpoints that may be therapeutically exploited in mitigating exacerbated disease in infected diabetics.